Controllability and null controllability of linear systems - I Davies; P Jackreece (Journal of Applied Sciences and Environmental Management, 2006)
This paper establishes sufficient conditions for the controllability and null controllability of linear systems. The aim is to use the variation of constant formula to deduce our controllability grammiam, by exploiting the properties of the grammiam and the asymptotic stability of the free system, we achieved our results. Journal of Applied Sciences and Environmental Management Vol. 9(3) 2005: 31-36